Improvement of Direct Interspecies Electron Transfer via Adding Conductive Materials in Anaerobic Digestion: Mechanisms, Performances, and Challenges - Chen, Le; Fang, Wei; Chang, Jianning; Liang, Jinsong; Zhang, Panyue; Zhang, Guangming (Frontiers in Microbiology, 2022)
Anaerobic digestion is an effective and sustainable technology for resource utilization of organic wastes. Recently, adding conductive materials in anaerobic digestion to promote direct interspecies electron transfer (DIET) has become a hot topic, which enhances the syntrophic conversion of various organics to methane. This review comprehensively summarizes the recent findings of DIET mechanisms with different mediating ways. Meanwhile, the influence of DIET on anaerobic digestion performance and the underlying mechanisms of how DIET mediated by conductive materials influences the lag phase, methane production, and system stability are systematically explored. Furthermore, current challenges such as the unclear biological mechanisms, influences of non-DIET mechanisms, limitations of organic matters syntrophically oxidized by way of DIET, and problems in practical application of DIET mediated by conductive materials are discussed in detail. Finally, the future research directions for practical application of DIET are outlined.